A downlink beamforming assisted by locally positioned communication devices. (24th June 2013) - You, Cheolwoo; Jung, Young‐Ho; Cho, Sunghyun
SUMMARY Recently, multiple cell types with overlapping coverage have been deployed simultaneously to increase cellular network capacity. Cross‐tier interference is one of the key technical challenges in the use of this method. A simple and practical beamforming scheme assisted by locally positioned communication devices for the downlink of a multi‐cell wireless hierarchical cell structure system is proposed in this paper to maximize the capacity of the embedded small cell and simultaneously ensure minimal impact on the performance of existing macrocells. The locally positioned communication devices can be implemented with low complexity and at low cost and can continuously provide helpful and accurate information to base stations for the proper configuration of geographical cell coverage, allowing neighboring cells to cooperate effectively with each other. Simulation results verify that the proposed scheme can provide a significant gain over conventional systems not using the proposed algorithm. Copyright © 2013 John Wiley & Sons, Ltd.